USE OF THE MAGNETIC STORM DST INDEX AS PRECURSOR OF MAJOR EARTHQUAKES IN INDONESIA FOR THE YEAR 2004-2018 - Hanif, Sayed
Earthquakes are natural disasters that occur naturally in the world and it is difficult to predict the location and time of an earthquake. Indonesia is geographically located in the ring of fire zone, where this area is very vulnerable to earthquakes that causes damage to buildings and even death. Several major earthquakes in Indonesia in 2004- 2018 include, Aceh Earthquake December 26 in 2004, Yogyakarta Earthquake May 27 in 2006, Sumatra Earthquake (Doublet) March 6 in 2007, the first Lombok Earthquake August 5 2018 and the second major earthquake 19 August 2018 and the last Palu Earthquake in 2018. This causes earthquake precursors, specifically magnetic precursors, to be helping disaster mitigation and being an early sign of an earthquake. In this study, observations were made of magnetic storm index data, especially the disturbance storm time (Dst) index for 33 days to 50 days before the main earthquake. Based on these events, it can be seen that the anomalies that occur are very diverse, such as the Aceh Earthquake with a visible anomaly reaching -374 nT, Yogyakarta Earthquake reaching -98 nT, Sumatran Doublet Earthquake anomaly reaching -49 nT, Lombok earthquake visible anomaly of -46 nT and The hammer anomaly is seen reaching -175 nT. The height of the anomaly can determine the earthquake damage that occurred, the lower the anomaly that is seen, the greater the possibility of earthquake damage that occurs, the higher the energy released by the earthquake, the clearer the visibility of anomaly..